2011
DOI: 10.1074/jbc.m111.294603
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cα Promotes Cell Migration through a PDZ-Dependent Interaction with its Novel Substrate Discs Large Homolog 1 (DLG1)

Abstract: Background: PKC␣ contains a unique PDZ ligand motif and is known to promote cellular migration. Results: PKC␣ binds and phosphorylates the scaffold DLG1; both proteins are necessary for cellular migration in non-small cell lung cancer cells. Conclusion: DLG1 coordinates PKC␣ signaling to promote cellular migration. Significance: Control of PKC␣ signaling mediated by scaffolds is crucial to promoting its downstream functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 55 publications
1
56
0
1
Order By: Relevance
“…PKC exerts an important effect on antiapoptosis and metastasis of NSCLC cells. Metastasis of NSCLC cells can be stimulated by the activation of PKC through a C-terminal class I PDZ-dependent interaction with its substrate, discs large homology-1 [291]. In addition, an increase in the activity of PKC and nuclear PKC has been detected in lung metastatic nodules originating from other cancers such as HCC [292].…”
Section: Small and Nonsmall Cell Lung Carcinomamentioning
confidence: 99%
“…PKC exerts an important effect on antiapoptosis and metastasis of NSCLC cells. Metastasis of NSCLC cells can be stimulated by the activation of PKC through a C-terminal class I PDZ-dependent interaction with its substrate, discs large homology-1 [291]. In addition, an increase in the activity of PKC and nuclear PKC has been detected in lung metastatic nodules originating from other cancers such as HCC [292].…”
Section: Small and Nonsmall Cell Lung Carcinomamentioning
confidence: 99%
“…PICK1 targets activated PKC␣ to synapses to phosphorylate the glutamate receptor subunit GluR2, leading to its endocytosis (77), but it can also act as a barrier to phosphorylation of the metabotropic glutamate receptor mGluR7a by PKC␣ (78). More recently, a family of Discs large homolog scaffolds that interact with the PDZ ligand of PKC␣ to facilitate cellular migration was also identified (79).…”
mentioning
confidence: 99%
“…In the same study, it was also shown that keratinocytes with silenced EPB41 exhibit reduced adhesion, cell spreading, migration, and motility. In addition, DLG1 has a role in wound healing, and it is proposed that the transglutaminase EPB41 binds to DLG1 (82). Ankyrin 1 could play a role in wound healing by initiating endothelial cell proliferation and/or adhesion via its interaction with CD44v10 and IP3 receptors on endothelial cell lipid rafts (83).…”
Section: Discussionmentioning
confidence: 99%